Affective neural circuits and inflammatory markers linked to depression and anxiety symptoms in patients with comorbid obesity. (April 2023) - Hallihan, Hagar; Tsai, Perry; Lv, Nan; Xiao, Lan; Peñalver Bernabé, Beatriz; Wu, Yichao; Pandey, Ghanshyam N.; Williams, Leanne M.; Ajilore, Olusola A.; Ma, Jun
Abstract: Although we have effective treatments for depression and anxiety, we lack mechanistic understanding or evidence-based strategies to tailor these treatments in the context of major comorbidities such as obesity. The current feasibility study uses functional neuroimaging and biospecimen data to determine if changes in inflammatory markers, fecal short-chain fatty acids, and neural circuit-based targets can predict depression and anxiety outcomes among participants with comorbid obesity. Blood and stool samples and functional magnetic resonance imaging data were obtained at baseline and 2 months, during the parent ENGAGE-2 trial. From 30 participants with both biospecimen and fMRI data, this subsample study explored the relationship among changes in inflammatory markers and fecal short-chain fatty acids and changes in neural targets, and their joint relationship with depression and anxiety symptoms. Bivariate and partial correlation, canonical correlation, and partial least squares analyses were conducted, with adjustments for age, sex, and treatment group. Initial correlation analyses revealed three inflammatory markers (IL-1RA, IL-6, and TNF-α) and five neural targets (in Negative Affect, Positive Affect, and Default Mode Circuits) with significantly associated changes at 2 months. Partial least squares analyses then showed that changes in IL-1RA and TNF-α and changes in three neural targets (in Negative Affect and Positive Affect Circuits) at 2 months were associated with changes in depression and anxiety symptoms at 6 months. This study sheds light on the plausibility of incorporation of inflammatory and gastrointestinal biomarkers with neural targets as predictors of depression and comorbid anxiety outcomes among patients with obesity. Highlights: Changes at 2 months in immune/short-chain fatty acid biomarkers were correlated with changes in specific neural targets. Correlations were found between Default Mode and Negative/Positive Affect neural targets; and IL-1RA, IL-6, and TNF-α. Changes in IL-1RA and TNA-α and in Negative/Positive Affect neural targets were predictors of depression and anxiety.